Massive Hemothorax Caused by a Single Intercostal Artery Bleed Ten Days after Solitary Minimally Displaced Rib Fracture. (5th November 2015) - Curfman, Karleigh R.; Robitsek, R. Jonathan; Salzler, Gregory G.; Gray, Katherine D.; Lapunzina, Charles S.; Kothuru, Ravi K.; Schubl, Sebastian D.
Abstract : Delayed hemothorax (DHX) following blunt thoracic trauma is a rare occurrence with an extremely variable incidence and time to diagnosis that is generally associated with clinically insignificant blood loss. In this report, we present a case of acute onset DHX ten days after a relatively mild traumatic event that resulted in a single minimally displaced rib fracture. The patient awoke from sleep suddenly with acute onset dyspnea and chest pain and reported to the emergency department (ED). The patient lost over six and a half liters of blood during the first 9 hours of his admission, the largest volume yet reported in the literature for DHX, which was eventually found to be due to a single intercostal artery bleed. Successful management in this case entailed two emergent thoracotomies and placement of multiple thoracostomy tubes to control blood loss. The patient was discharged home on postoperative day 5.